Investigation of the fluid behavior of asphaltenes and toluene insolubles by high-temperature proton nuclear magnetic resonance and rheometry and their application to visbreaking - Castro-Díaz, M.; Uguna, Clement N.; Cheeseman, Barry; Barker, James; Snape, C.E. (American Chemical Society, 2016)
The fluid behavior of asphaltenes at elevated temperatures impacts coke formation in a number of hydrocarbon conversion processes, including visbreaking and delayed coking. In this study, the asphaltenes from a number of sources, namely, a vacuum residue, a petroleum source rock (Kimmeridge clay) bitumen obtained by hydrous pyrolysis, and bitumen products from a sub-bituminous coal and pine wood obtained by thermolytic solvent extraction using tetralin, have been characterized using high-temperature proton nuclear magnetic resonance (1H NMR), and the results correlated with those from small-amplitude oscillatory shear rheometry. Further for comparison, the coke (toluene insolubles) obtained from visbreaking the vacuum residue was also characterized. All of the asphaltenes became completely fluid by 300 °C, with hydrogen being completely mobile with coke formation, identified as a solid phase, not occurring to a significant extent until 450 °C. Extremely good agreement was obtained between high-temperature 1H NMR and rheometry results, which confirmed that the asphaltenes were highly fluid from 300 °C, with initial signs of resolidification being observed at temperatures of around 450 °C. During softening, extremely good correlations between fluid hydrogen and phase angle were obtained as the asphaltenes softened. The toluene insolubles however did contain some fluid material; thus, it cannot be regarded as strictly solid coke, but clearly, with increasing temperature, the fluid material did convert to coke. Under actual process conditions, this fluid material could be responsible for coke adhering to reactor surfaces.